2020
DOI: 10.1155/2020/7679147
|View full text |Cite
|
Sign up to set email alerts
|

Successful Kidney Transplantation in a Recipient Coinfected with Hepatitis C Genotype 2 and HIV from a Donor Infected with Hepatitis C Genotype 1 in the Direct-Acting Antiviral Era

Abstract: Despite significant advances in transplantation of HIV-infected individuals, little is known about HIV coinfected patients with hepatitis C virus (HCV) genotypes other than genotype 1, especially when receiving HCV-infected organs with a different genotype. We describe the first case of kidney transplantation in a man coinfected with hepatitis C and HIV in our state. To our knowledge, this is also the first report of an HIV/HCV/HBV tri-infected patient with non-1 (2a) HCV genotype who received an HCV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…68 A single report of successful kidney transplantation from an HCV genotype 1a donor into a recipient with HIV and HCV genotype 2a, and subsequent clearance of HCV by treatment with DAAs, illustrates the feasibility of this approach and the advantage of reduced waiting time for transplant. 69 A simulation comparing the 2 strategies, pretransplant versus posttransplant treatment, concluded that treatment posttransplant was consistently cost-saving because of the high cost of dialysis. 70 Among patients with low fibrosis liver disease (F0-F1), treatment posttransplant also yielded higher life months and quality-adjusted life months, except among F1 candidates with wait times ≥18 mo.…”
Section: Pretransplant Evaluation and Optimization For Transplantmentioning
confidence: 99%
“…68 A single report of successful kidney transplantation from an HCV genotype 1a donor into a recipient with HIV and HCV genotype 2a, and subsequent clearance of HCV by treatment with DAAs, illustrates the feasibility of this approach and the advantage of reduced waiting time for transplant. 69 A simulation comparing the 2 strategies, pretransplant versus posttransplant treatment, concluded that treatment posttransplant was consistently cost-saving because of the high cost of dialysis. 70 Among patients with low fibrosis liver disease (F0-F1), treatment posttransplant also yielded higher life months and quality-adjusted life months, except among F1 candidates with wait times ≥18 mo.…”
Section: Pretransplant Evaluation and Optimization For Transplantmentioning
confidence: 99%